The Trace of Cervanters in the Royal Collection of Photography (Estudios de Historia de España, 2019)
The celebration of the fourth centenary of Michael of Cervantes Saavedra’s death offers to us the opportunity to announce the whole photographic corpus generated concerning the diverse facets reached by Cervantine iconography. His study has allowed us to identify correctly some of the images that are the classic one in the History of Spanish Photography.
Keywords: Cervantes; Photography; Cervantes’s house